The Nickel Boys’ Elwood through the Scope of Joseph Campbell’s Hero’s Journey - Hopkins, Wesley Allan (Journal of English Language and Literature (ISSN: 2368-2132), 2020)
This paper examines The Nickel Boys’ main character Elwood, explaining that his story is an accurate representation of Joseph Campbell’s hero’s journey or “monomyth.” It explains the stages of the hero’s journey and compares them to moments in Elwood’s story.